2009
DOI: 10.1186/1471-2199-10-46
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ColR binding consensus and prediction of regulon of ColRS two-component system

Abstract: Background: Conserved two-component system ColRS of Pseudomonas genus has been implicated in several unrelated phenotypes. For instance, deficiency of P. putida ColRS system results in lowered phenol tolerance, hindrance of transposition of Tn4652 and lysis of a subpopulation of glucose-grown bacteria. In order to discover molecular mechanisms behind these phenotypes, we focused here on identification of downstream components of ColRS signal transduction pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…Previous studies have shown that despite being preceded by a ColR binding site, the colR promoter is not autoregulated and this site is associated only with the regulation of PP0900, located upstream of colR [40]. However, as this data was obtained under non-inducing conditions, we tested whether the expression of the colRS operon may respond to metal excess.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that despite being preceded by a ColR binding site, the colR promoter is not autoregulated and this site is associated only with the regulation of PP0900, located upstream of colR [40]. However, as this data was obtained under non-inducing conditions, we tested whether the expression of the colRS operon may respond to metal excess.…”
Section: Resultsmentioning
confidence: 99%
“…campestris (47). Thus, ColR/ColS is involved in maintaining the structural integrity and function of the outer membrane (23,24) and contributes to X. citri subsp. citri growth in planta.…”
Section: Discussionmentioning
confidence: 99%
“…ColRS-CprRS homologues were defined initially for P. fluorescens, in which the ColRS system is required for Pm tolerance and efficient root colonization of host plants (45,60) and subsequently for P. putida, in which this system is required for root colonization (46), specific transpositional activity (61), phenol tolerance (62,63), heavy metal tolerance (64), and protection against cell lysis in the context of metabolic responses to glucose limitation (63,65). Interestingly, oprF (PA1777) and crc (PA5332) mediate this metabolic response in P. putida (65), and ColRS also regulates the gene product of pagL (PA4661), a lipid A deacylase, in this organism (66). The present work has implicated all three of these loci in P. aeruginosa Pm resistance.…”
Section: Discussionmentioning
confidence: 99%